Two Countries, One Crisis: The YO-VID22 Pandemic Study (University of Maribor Press, 2025)
The publication analyzes the experiences, values, and well-being of young people in Croatia and Slovenia before, during, and after the Covid-19 pandemic. The results show that the pandemic worsened physical and mental health, with young women being the most affected. In addition to stress, social isolation intensified, strongly reinforcing feelings of loneliness, while housing and financial barriers limited independence, especially among disadvantaged and urban youth. Mental health problems, particularly stress, depression, and burnout, remain widespread, and the pandemic further exacerbated these issues. In this context, Croatian youth report stronger family support, whereas Slovenian youth experienced more tension within the family environment. Regarding political participation, Croatian youth are evidently disappointed and passive, while Slovenian youth are more active. A general decline in trust and solidarity in both groups points to the need for inclusive policies to improve youth well-being.